Proteomic Characterization of Proliferation Inhibition of Well-Differentiated Laryngeal Squamous Cell Carcinoma Cells Under Below-Background Radiation in a Deep Underground Environment - Liu, Jifeng; Ma, Tengfei; Gao, Mingzhong; Liu, Yilin; Liu, Jun; Wang, Shichao; Xie, Yike; Wen, Qiao; Wang, Ling; Cheng, Juan; Liu, Shixi; Zou, Jian; et al. (Frontiers in Public Health, 2020)
Background: There has been a considerable concern about cancer induction in response to radiation exposure. However, only a limited number of studies have focused on the biological effects of below-background radiation (BBR) in deep underground environments. To improve our understanding of the effects of BBR on cancer, we studied its biological impact on well-differentiated laryngeal squamous cell carcinoma cells (FD-LSC-1) in a deep underground laboratory (DUGL). Methods: The growth curve, morphological, and quantitative proteomic experiments were performed on FD-LSC-1 cells cultured in the DUGL and above-ground laboratory (AGL). Results: The proliferation of FD-LSC-1 cells from the DUGL group was delayed compared to that of cells from the AGL group. Transmission electron microscopy scans of the cells from the DUGL group indicated the presence of hypertrophic endoplasmic reticulum (ER) and a higher number of ER. At a cutoff of absolute fold change ≥ 1.2 and p < 0.05, 807 differentially abundant proteins (DAPs; 536 upregulated proteins and 271 downregulated proteins in the cells cultured in the DUGL) were detected. KEGG pathway analysis of these DAPs revealed that seven pathways were enriched. These included ribosome (p < 0.0001), spliceosome (p = 0.0001), oxidative phosphorylation (p = 0.0001), protein export (p = 0.0001), thermogenesis (p = 0.0003), protein processing in the endoplasmic reticulum (p = 0.0108), and non-alcoholic fatty liver disease (p = 0.0421). Conclusion: The BBR environment inhibited the proliferation of FD-LSC-1 cells. Additionally, it induced changes in protein expression associated with the ribosome, gene spliceosome, RNA transport, and energy metabolism among others. The changes in protein expression might form the molecular basis for proliferation inhibition and enhanced survivability of cells adapting to BBR exposure in a deep underground environment. RPL26, RPS27, ZMAT2, PRPF40A, SNRPD2, SLU7, SRSF5, SRSF3, SNRPF, WFS1, STT3B, CANX, ERP29, HSPA5, COX6B1, UQCRH, and ATP6V1G1 were the core proteins associated with the BBR stress response in cells.